Cementless modular intramedullary nail without bone-on-bone fusion as a salvage procedure in chronically infected total knee prosthesis: long-term results - Scarponi, Sara (Springer Berlin Heidelberg, 2013)
PURPOSE: Our purpose was to evaluate long-term results of two-stage cementless intramedullary nailing without achieving bone-to-bone fusion for treating chronically infected total knee arthroplasty (TKA). METHODS: Thirty-eight patients treated according to the same protocol were retrospectively evaluated for clinical, functional, laboratory and radiological outcomes. RESULTS: Spacer exchange was necessary for infection persistence in one case. At a minimum two year follow-up, 34 patients (89.5 %) showed no infection recurrence; among these 34 patients, 29 (85.3 %) reported no or moderate pain [visual analogue scale (VAS) ≤3]; mild to moderate handicap (Lequesne Algofunctional Index < 7.5) was observed in 18 patients (52.9 %). No patient underwent revision for aseptic loosening, and no nail breakage was observed. CONCLUSIONS: Two-stage cementless intramedullary nailing without achieving bone-to-bone fusion is a viable option for treating chronically infected TKA in selected, complex cases.